Kedudukan Hukum Perjanjian Nominee dalam Sistem Hukum Perdata Indonesia - I Made Angga Legawa; Anak Agung Istri Eka Krisna Yanti (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This research examines the legal status of nominee agreements within Indonesia's civil law system and their legal consequences for the parties involved. Amid increasing foreign investment in Indonesia, the phenomenon of nominee agreements has created tension between global economic interests and the principle of nationalism in land ownership. Using normative legal research methods with statutory and conceptual approaches, this research analyzes nominee agreements within the framework of the Indonesian Civil Code and the Basic Agrarian Law. The findings reveal that nominee agreements have no valid legal status as they contradict Articles 21 and 26 paragraph (2) of the Basic Agrarian Law and fail to fulfill the lawful cause requirement under Article 1320 of the Civil Code. Doctrinally, these agreements fall under the category of absolute nullity (void ab initio) as they constitute a form of legal circumvention (fraus legis). The legal consequences for all parties are detrimental, Indonesian citizens acting as nominees potentially face criminal charges and loss of land rights, while foreign citizens as beneficial owners have no legal protection for their investments.